Neonatal Tetanus - H. Tjandra; M. Munir (Paediatrica Indonesiana, 1978)
Analysis of 108 cases of Neonatal Tetanus by using a scoring system (Tjandra et al., 1974) revealed that 18 patients belonged to Grade I with a mortality rate of 5.6%; 43 belonged to Grade II with a mortality nate of 58.1%; and 47 belonged to Grade III with 91.5% mortality. The differences of mortality between the 3 groups are statistically significant. Mortality rate of 1973 was the lowest (50%) compared to that of 1972 (75%); 1974 (72.2%) and 1975 (61.4%). However, the number of patients belonging to Grade I in 1973 was the highest, 36.4%; whereas that of 1972 was 16.7%; 1974 was 11.1% and 1975 was 9.1 %. Classification of severity in Neonatal Tetanus is therefore, not only important for selecting a "treatment of choice" by comparing mortality rates of those having the same grade of severity, but may be also very useful in determining the method of treatment for different levels of severity.